Translation, cross-cultural adaptation, validity and reliability of the inaugural Albanian Roland-Morris Disability Questionnaire in Albanian population with low back pain - Orges Lena; Enkeleda Gjini; Jasemin Todri (PLoS ONE, 2025)
Background context To precisely evaluate the disability resulting from low back pain and the efficacy of interventions, it is essential to utilize a standardized instrument capable of measuring the patient’s condition changes over time. One of the most frequently utilized self-administered standardized questionnaires is the Roland Morris Disability Questionnaire (RMDQ). Purpose To culturally adapt the RMDQ into Albanian and assess its psychometric properties within an Albanian population. Study design: Observational Patient sample: The total sample consisted of 200 individuals diagnosed with various conditions including persistent low back pain, coxofemoral luxation, back trauma, lumbar fracture, and arthritis. Outcome measures: The RMQ consists of 24 individual items each presented as a single sentence. The maximum achievable score is 24, while the minimum is 0. Methods The research procedure involved two phases: initially, the translation and cultural adaptation, and subsequently, the assessment of quality within a clinical investigation. Test-retest reliability at 7 days was evaluated in 200 participants. Results Kappa statistics showed that Alb-RMDQ had acceptable item-by-item agreement for 11 items (k = 0.603–0.755) and the remaining 13 were moderate agreement (k = 0.464–0.595). The exploratory factor analysis (EFA) of Albanian version was used to determine this dimensionality. An initial EFA analysis with a principal component analysis using Varimax with Kaiser Normalization rotation method resulted in a 10-factor structure with a KMO = 0.465 and a Chi-square = 461.791, p = 0.000. The Interclass Correlation Coefficient (ICC) between the first and the second evaluation for each item performed with two mixed effect model was between 0.621–0.938 using an absolute agreement definition. Conclusions The AlbRMDQ version of RMDQ has a good validity and reliability and may be an important outcome tool for the clinical and research purpose for the Albanian speaking population.